2020
DOI: 10.1007/s12144-020-01007-5
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of the psychometric properties of the contingencies of self-worth scale (CSWS)

Abstract: The Contingencies of Self-Worth Scale (CSWS) is a widely used personality self-report questionnaire developed for measuring the domains in which self-esteem is sustained by successes and achievements as well as threatened by obstacles and failures. Two studies (Nstudy1 = 453, Nstudy2 = 293) aimed to further refine our knowledge of its psychometric properties. Results attested that, at the first-order level, the originally hypothesized seven-factor model proved to be the best-fitting one, but the inclusion of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Nested models were compared by using the DIFFTEST option in Mplus, which allows for models' comparison using the WLSMV estimator. Non-nested models were instead compared by comparing the associated values assumed by an adapted version of the AIC for the WLSMV estimator see [97], using the following formula [98]: ∆AIC = AICi-AICmin, where AICmin is the minimum observed AIC between the two models. Burnham and Anderson [99] suggested that ∆AIC < 2 means that the models have comparable fit.…”
Section: Discussionmentioning
confidence: 99%
“…Nested models were compared by using the DIFFTEST option in Mplus, which allows for models' comparison using the WLSMV estimator. Non-nested models were instead compared by comparing the associated values assumed by an adapted version of the AIC for the WLSMV estimator see [97], using the following formula [98]: ∆AIC = AICi-AICmin, where AICmin is the minimum observed AIC between the two models. Burnham and Anderson [99] suggested that ∆AIC < 2 means that the models have comparable fit.…”
Section: Discussionmentioning
confidence: 99%